Feasibility of Traditional Red Dragon Fruit Skin Mask (Hylocereus polyrhizus) for Dry Facial Skin Care - Fariadi, Angellica; Minerva, Prima (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Dry skin is one of the problematic skins that causes a lack of self-confidence, dry skin is caused by exposure to direct sunlight and low water content in the skin. Dry skin can be prevented with care from the outside and from the inside. Traditional masks are cosmetics that function to increase blood circulation to the skin and provide moisture to the skin. Red dragon fruit peel has benefits in providing moisture and contains antioxidants that are good for the skin and are not widely known to the public. This study aims to analyze the feasibility of traditional red dragon fruit peel masks for dry facial skin care in terms of chemical content, texture, aroma, adhesion, and panellist preferences. This research is experimental research with a quantitative description design. The research instruments are laboratory tests, organoleptic tests, and hedonic tests. Collecting data using the method of documentation and questionnaires compiled with a Likert scale. Descriptive data analysis percentage to determine the feasibility of traditional red dragon fruit peel masks seen from the texture, aroma, stickiness, and preference of the panellists. The results of the laboratory test showed that the content of vitamin A was 1.95 gr/100 gr and Vitamin C was 0.66 gr/100 gr. The results of the organoleptic test were 71,42% fine textured, 42.85% had a very distinctive aroma of red dragon fruit peel, 42.85% was sticky, and 57.14% was favoured by the panellists.